Murder at an Irish castle - Brannigan, Ellie (Brannigan, Ellie. Irish castle mystery, 2023)
"Rodeo Drive bridalwear designer Rayne McGrath expected her thirtieth birthday to start with a power lunch and end with champagne, lobster, and a diamond engagement ring from her fiancé. Instead, flat-broke and busted, she's on a plane to Ireland, where she discovers that she's inherited a run-down family castle. Uncle Nevin's will contains a few caveats--for example, if Rayne doesn't turn McGrath Castle around within a year, the entire village will be financially destroyed. With the fate of the town in her hands and rumors that Rayne's uncle's death wasn't actually an accident, she can't possibly go back to her old life in L.A. As the devastating truth about her uncle dawns on Rayne, it's not just her reputation that's on the line; it's her life"--Page 4 of cover.